2018
DOI: 10.1111/jabr.12123
|View full text |Cite
|
Sign up to set email alerts
|

The central sensitization inventory: A user’s manual

Abstract: The Central Sensitization (CSI) Inventory was introduced in 2012. It was initially intended as a screener to help identify when presenting symptoms may be related to central sensitization or indicate the presence of a central sensitivity syndrome. It has now been translated and validated in a number of European, Asian, and South American languages. This article provides an overview of CSI rationale, development, recommended uses, and research results, including evidence of validity and reliability, in clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 78 publications
(142 reference statements)
3
70
0
Order By: Relevance
“…The CSI has been psychometrically evaluated in English and other Asian, South American, and European languages. It has been found to be psychometrically sound in all published cross‐cultural studies to the present, with test‐retest reliability coefficients from 0.85 to 0.99 and Cronbach’s alpha from 0.88 to 0.99 5–7 . Evidence of convergent, discriminant, and predictive validity, using both subjective (eg, patient‐reported) and objective (including quantitative sensory testing, brain gamma aminobutyric acid levels, serum brain‐derived neurotrophic factor) CS‐related variables, have been found in a number of previous studies using multiple‐language versions of the CSI 5,8 .…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…The CSI has been psychometrically evaluated in English and other Asian, South American, and European languages. It has been found to be psychometrically sound in all published cross‐cultural studies to the present, with test‐retest reliability coefficients from 0.85 to 0.99 and Cronbach’s alpha from 0.88 to 0.99 5–7 . Evidence of convergent, discriminant, and predictive validity, using both subjective (eg, patient‐reported) and objective (including quantitative sensory testing, brain gamma aminobutyric acid levels, serum brain‐derived neurotrophic factor) CS‐related variables, have been found in a number of previous studies using multiple‐language versions of the CSI 5,8 .…”
Section: Introductionsupporting
confidence: 61%
“…It has been found to be psychometrically sound in all published cross‐cultural studies to the present, with test‐retest reliability coefficients from 0.85 to 0.99 and Cronbach’s alpha from 0.88 to 0.99 5–7 . Evidence of convergent, discriminant, and predictive validity, using both subjective (eg, patient‐reported) and objective (including quantitative sensory testing, brain gamma aminobutyric acid levels, serum brain‐derived neurotrophic factor) CS‐related variables, have been found in a number of previous studies using multiple‐language versions of the CSI 5,8 . Differences in CSI scores have been found among patient groups and healthy controls, as well as among patient subgroups (including those with acute pain, chronic pain, and specific disorders such as fibromyalgia) 5 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Higher dosages of analgesics and higher pain intensity correlated with higher CSI scores post‐surgically. Neblett, however, pointed out that a CSI score of <40 can be present in patients with CSS, and Tanaka et al identified patients diagnosed with CSSs who scored <40 on the CSI. Moreover, CSI cutoff scores seem to be culturally sensitive, since pain behavior is influenced not only by psychosocial factors but also by cultural ones .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple language versions are available at: http://www.pridedallas.com/questionnaires. Neblett (this Issue) has provided a “User's Manual” for the CSI in this SPECIAL ISSUE.…”
Section: Assessment Methods For Central Sensitizationmentioning
confidence: 99%